Data from: Natural history of limb girdle muscular dystrophy R9 over 6 years: searching for trial endpoints - Murphy, Alexander P.; Morrow, Jasper; Dahlqvist, Julia R.; Stojkovic, Tanya; Willis, Tracey A.; Sinclair, Christopher D. J.; Wastling, Stephen; Yousry, Tarek; Hanna, Michael S.; James, Meredith K.; Mayhew, Anna; Eagle, Michelle; et al. (Dryad, 2019)
Objective: Limb girdle muscular dystrophy type R9 (LGMD R9) is an
autosomal recessive muscle disease for which there is currently no
causative treatment. The development of putative therapies requires
sensitive outcome measures for clinical trials in this slowly progressing
condition. This study extends functional assessments and MRI muscle fat
fraction measurements in an LGMD R9 cohort across 6 years. Methods:
Twenty‐three participants with LGMD R9, previously assessed over a 1‐year
period, were re‐enrolled at 6 years. Standardized functional assessments
were performed including: myometry, timed tests, and spirometry testing.
Quantitative MRI was used to measure fat fraction in lower limb skeletal
muscle groups. Results: At 6 years, all 14 muscle groups assessed
demonstrated significant increases in fat fraction, compared to eight
groups in the 1‐year follow‐up study. In direct contrast to the 1‐year
follow‐up, the 6‐min walk test, 10‐m walk or run, timed up and go, stair
ascend, stair descend and chair rise demonstrated significant decline.
Among the functional tests, only FVC significantly declined over both the
1‐ and 6‐year studies. Interpretation: These results further support fat
fraction measurements as a primary outcome measure alongside functional
assessments. The most appropriate individual muscles are the vastus
lateralis, gracilis, sartorius, and gastrocnemii. Using composite groups
of lower leg muscles, thigh muscles, or triceps surae, yielded high
standardized response means (SRMs). Over 6 years, quantitative fat
fraction assessment demonstrated higher SRM values than seen in functional
tests suggesting greater responsiveness to disease progression.
LGMD R9 Murphy Annals Clin Trans Neurol 2019 public 200319Anonymised MRI
measurements (fat fraction), physical function tests and basic subject
characteristics as described in the Data Availability statement of Murphy
et al. (2019)
Keywords: Functional Assessments; LGMD2I; Dixon fat fraction; Limb girdle muscular dystrophy; LGMD R9; Quantitative MRI; Clinical Trial Methodology; natural history